2005
DOI: 10.1074/jbc.m412304200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Microtubule-associated Protein-2 and p63

Abstract: Neurons are polarized cells presenting two distinct compartments, dendrites and an axon. Dendrites can be distinguished from the axon by the presence of rough endoplasmic reticulum (RER). The mechanism by which the structure and distribution of the RER is maintained in these cells is poorly understood. In the present study, we investigated the role of the dendritic microtubuleassociated protein-2 (MAP2) in the RER membrane positioning by comparing their distribution in brain subcellular fractions and in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 76 publications
3
35
0
Order By: Relevance
“…The SER random tubular network is characterised by highly convoluted tubules rather than by the relatively straight ones of the polygonal meshwork and could thus represent a spontaneous arrangement of the ER -similar to the so-called 'sponge phase' of curvature theoreticians (Hyde et al, 1997) -that is attained in the absence of regulatory factors mediating interaction with microtubules. Consistently, CLIMP-63, a membrane protein that mediates static interaction of the RER with microtubules (Farah et al, 2005;Klopfenstein et al, 1998;Schweizer et al, 1995) was excluded from the interior of the SER patches. On the basis of the considerations above, we propose a model for the PDMP-induced formation of SER patches, illustrated in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The SER random tubular network is characterised by highly convoluted tubules rather than by the relatively straight ones of the polygonal meshwork and could thus represent a spontaneous arrangement of the ER -similar to the so-called 'sponge phase' of curvature theoreticians (Hyde et al, 1997) -that is attained in the absence of regulatory factors mediating interaction with microtubules. Consistently, CLIMP-63, a membrane protein that mediates static interaction of the RER with microtubules (Farah et al, 2005;Klopfenstein et al, 1998;Schweizer et al, 1995) was excluded from the interior of the SER patches. On the basis of the considerations above, we propose a model for the PDMP-induced formation of SER patches, illustrated in Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The function of HMWMAP2 on the surface of RER membranes is most likely to anchor these membranes to microtubules and thereby to contribute to their segregation in the somato-dendritic compartment [Bartlett and Banker, 1984a,b;Peters et al, 1991]. We showed that the interaction of HMWMAP2 with CLIMP-63 is necessary for the association of RER membranes with microtubules in an in vitro assay [Farah et al, 2005]. Several studies reported that the ER membranes are associated with microtubules [Terasaki et al, 1986;Terasaki, 1990;Terasaki and Reese, 1994;Hirokawa, 1998;Aihara et al, 2001].…”
Section: Segregation Of Rer Membranes In the Somato-dendritic Compartmentioning
confidence: 81%
“…The mechanisms underlying the segregation and/or the maintenance of the RER membranes in this neuronal compartment seem to involve HMWMAP2. In a recent study, we reported that HMWMAP2 are associated with the rough endoplasmic reticulum (RER) [Farah et al, 2005] and that this association is mediated by the interaction of the HMWMAP2 projection domain with the RER protein termed cytoskeleton-linking membrane protein-63 (CLIMP-63). CLIMP-63 is an integral membrane protein that links RER membranes to microtubules in non-neuronal cells [Klopfenstein et al, 1998].…”
Section: Segregation Of Rer Membranes In the Somato-dendritic Compartmentioning
confidence: 99%
“…The following mammalian expression plasmids have been described: pGW1-EB3-GFP (Jaworski et al, 2009), pGW1-GFP, p␤actin-HA-␤-galactosidase (Hoogenraad et al, 2005), pSuper vector (Brummelkamp et al, 2002), pSuper-EB3-shRNA (Jaworski et al, 2009), GFP-MAP2c (Farah et al, 2005), NR2B-shRNA and NR2A-shRNAs (Kim et al, 2005), mCherry-␣-tubulin (Shaner et al, 2004), and GST-EB3 (Komarova et al, 2005). GFP-KIFC2 was generated by PCR cloning full-length rat KIFC2 cDNA into pEGFP-C1.…”
Section: Expression Constructsmentioning
confidence: 99%